Virtual Reality-Based Learning Media for Enhancing Computational Thinking in Junior High Schools - Hardika Dwi Hermawan; Adira Bintang Permana; Dias Aziz Pramudita (Dinasti Publisher, 2025)
This study developed and evaluated Bytethink7, a Virtual Reality (VR)-based learning medium to improve Computational Thinking (CT) skills among seventh-grade students at SMP Negeri 3 Jatipuro, Indonesia. The application was designed using the 4D model (Define, Design, Develop, Disseminate) and developed with Unity3D, SketchUp, Blender, Vroid, and Adobe Photoshop. Validation by two media experts and two subject matter experts yielded highly satisfactory results, with a Likert score of 86.25%, Aiken’s V of 0.825 (very high content validity), and all content criteria met according to the Guttman scale (100%). Black-box functionality testing showed the application runs perfectly (100%), while testing with 22 students yielded an average System Usability Scale (SUS) score of 74, categorized as “Good/Acceptable.” These findings indicate that Bytethink7 is effective as an interactive learning medium that supports the constructivist learning-by-doing principle and can serve as a solution to the lack of CT learning tools at the junior high school level. Further research is recommended to test its impact on CT skill attainment and compare it with other educational technologies.